2017
DOI: 10.1097/md.0000000000007950
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine as an adjuvant to ropivacaine for wound infiltration in patients undergoing open gastrectomy

Abstract: Objectives:The primary objective of this study was to investigate whether dexmedetomidine could potentiate the analgesic efficacy of ropivacaine, when added to ropivacaine for wound infiltration in patients undergoing open gastrectomy.Methods:Fifty patients scheduled for open gastrectomy were divided into 2 equal groups that were received wound infiltration using 20 mL 0.3% ropivacaine plus 2 mL normal saline (group R) or 20 mL 0.3% ropivacaine plus 2 mL 1.0 μg/kg dexmedetomidine (group DR). Visual analogue sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The search identified 251 studies, of which 198 were eliminated from further review because of not controlled trials or were duplications; after reviewing the abstracts, an additional 48 trials were excluded because they were not relevant to our study. Finally, the articles considered to be suitable for the meta‐analysis consisted of five RCTs, enrolling a total of 294 adult patients. The search process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search identified 251 studies, of which 198 were eliminated from further review because of not controlled trials or were duplications; after reviewing the abstracts, an additional 48 trials were excluded because they were not relevant to our study. Finally, the articles considered to be suitable for the meta‐analysis consisted of five RCTs, enrolling a total of 294 adult patients. The search process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Of the five studies, two studies were from India, two studies were from China, and one study was from Egypt. Four studies involved local wound infiltration at the end of the operation, and one study concerned local wound infiltration before the operation. Among them, local anaesthetics were ropivacaine in three studies, and bupivacaine in the other two studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound infiltrative analgesia is a standard method of providing analgesia in surgical patients especially following laparoscopic cholecystectomy (6) . Previous studies have shown that dexmedetomidine is an effective adjuvant to bupivacaine in wound infiltrative analgesia following open surgeries (7,8) . Recent study has shown that dexmedetomidine is an effective adjuvant to ropivacaine following laparoscopic cholecystectomy (8) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dexmedetomidine is an effective adjuvant to bupivacaine in wound infiltrative analgesia following open surgeries (7,8) . Recent study has shown that dexmedetomidine is an effective adjuvant to ropivacaine following laparoscopic cholecystectomy (8) . This study also showed that dexmedetomidine when used as an adjuvant improves quality of analgesia as well as increases early ambulation with effective pain management.…”
Section: Discussionmentioning
confidence: 99%